Migrant families and Children’s inclusion in culturally diverse educational contexts in Spain - Onsès-Segarra, Judit; Carrasco-Segovia, Sara; Sancho-Gil, Juana M. (Frontiers in Education, 2023)
This paper builds on the European project MiCREATE, which aimed to explore and stimulate migrant children and youth reception and inclusion in educational and social systems by adopting a child-centred approach at educational practice and policy levels. We focus on the role of the students’ local and immigrant families in this often-challenging process. We have evidence of the vital role of families in children and youth education. However, research mainly focuses on teachers when discussing issues related to the reception and inclusion of migrant students in schools, often forgetting that families and children/youth are also critical elements in these processes. In this project, we have explored the roles expected and developed by local and foreign families in facilitating and accompanying schools and students on these not-always-easy paths using various methods and activities. This paper focuses on aspects of the MiCREATE project related to the crucial role of families in their children’s social and educational experiences in the host country. It is based on fieldwork carried out in 16 schools in Spain, including teachers, families, students, educational community members and policymakers. Art-based research methods, open-ended interviews and focus groups provided a broad picture of the different views and expectations of all those involved in formal education. From the thematic analysis of the participants’ contributions, results emerge around two main focuses: (1) difficulties migrant families face in getting involved in school life, such as cultural clashes, school segregation, migrant families’ environment and the difference between primary school and secondary schools; (2) more general and specific initiatives that facilitate migrant family involvement in school life.